Usp11 maintained the survival of marginal zone B cells under ionizing radiation by deubiquitinating DLL1 and JAG2 - Jiaqi Sheng; Depei Wu; Jingzhe Shang; Xiaodan Fu; He Gao; Jianjie Rong; Jun Wang; Jiancheng Hu; Xiaofei Qi (Cell Death and Disease)
Abstract Efficacy of radiation therapy is compromised by hematopoietic and immune impairments, with elusive underlying causes. This study aimed to elucidate Usp11’s role in radiation-induced injuries and uncover related mechanisms. Utilized ARS mouse model to observe survival rates of Usp11−/− (KO) mice post-TBI (Total Body Irradiation). Assessed lymphocyte and MZ B (Marginal Zone B) cell rates using histological analysis, single-cell sequencing, immunofluorescence (IF), immunohistochemistry (IHC), and flow cytometry (FCM). Conducted Co-IP and ubiquitination experiments for mechanism elucidation. Quantified IgM and IgG using ELISA and FC. Explored public databases for potential correlation molecules. Our findings indicated that Usp11−/− mice exhibited improved survival rates following TBI, with the spleen playing a pivotal role. HE staining revealed a wider marginal zone in the spleen of Usp11+/+ mice post-irradiation. Single-cell sequencing, IF, IHC, and FCM analyses revealed a higher survival rate of MZ B cells in Usp11−/− mice after irradiation. Furthermore, treatment with the Usp11 inhibitor, mitoxantrone, successfully targeted and inhibited Usp11, thereby alleviating the reduction in MZ B cells in the spleen following total body irradiation. Mechanistically, Usp11 sustained the survival of MZ B cells by regulating the ubiquitination of Notch’s ligands, DLL1 and JAG2, thereby promoting immune cell remodeling in the spleen. In conclusion, Usp11 played a crucial role in modulating immune system damage induced by ionizing radiation, primarily through ubiquitination of Notch ligands. This study provides insights into radiation-induced immune injuries and suggests Usp11 as a potential therapeutic target.